Enhancement study of electronic component size measurement and defect detection based on machine vision - Yi Jiang; Shamsul Arrieya Ariffin; Yanbei Duan (AIP Advances, 2025)
This paper is based on machine vision technology, combined with Halcon software, based on electronic components’ size measurement and defect detection. First, the application status and research significance of machine vision technology in the field of electronic components are introduced. The camera model MV-SUA1201C is used to take the image of the calibration board and then calibrate the industrial camera through HALCON to obtain the relationship between the world coordinates and the pixel coordinates. Then, the electronic component images were pre-processed, such as grayscale conversion, and the preprocessed images were used for size measurement and defect detection. Size measurement is the automatic measurement of electronic components by adding components to the measurement model. Defect detection is to automatically identify the starting position of the pin, detect each pin one by one, and automatically mark the missing position of the pin. The pin detection result is displayed by the upper machine. Finally, the relative error of the visual measurement results is controlled at about 0.8%, and the visual defect detection can automatically detect the pin defect, saving both manpower and time cost.